THE FEASIBILITY OF USING SCIENTIFIC TECHNIQUES TO ASSESS REPAIR-MATERIAL SUITABILITY IN EARTHEN BUILDING CONSERVATION - Stephenson, Victoria; Fodde, Enrico (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The application of scientiic techniques to conservation work has in recent years grown as a discipline, driven by a desire within the ield of building conservation to better understand historic building materials. Wide ranges of historic materials are now analyzed to determine behavior and performance characteristics, which has led to advancements in the implementation of conservation work. However, the area of earthen building conservation has not yet been investigated in great detail; there is at present a large lacuna on how to select earthen repair materials, especially in terms of sacriiciality of interventions. This study directly addresses this fact by carrying out laboratory analysis of earthen materials in order to assess the feasibility of using repair materials to specify conservation work. A case study from Buckinghamshire in England was chosen; a wychert-cob ecclesiastical building that had recently undergone repair and conservation. An identical program of material classiication and performance tests was carried out on two sample materials from the building; one historic and one repair material. Through the study of laboratory results, the material characteristics and mechanical behavior of the two earthen materials were compared, and a critical analysis of the compatibility of the historic and repair material carried out. The indings of the study concluded that the repair material was unsuitable for use in this case, being incompatible with the original material. The achievement of the work was twofold; irstly it serves as veriication for using these techniques to obtain comparable results that can be used to appraise material sacriiciality, and secondly it demonstrates that earthen materials are of a complexity whereby compatibility cannot be assumed using basic techniques. Work such as this highlights the need for analytical investigations in earthen building conservation, in order to ensure appropriate repair materials and techniques are used.